Respostas
respondido por:
4
(y / 2 + 1 / 3 )² - (y / 2 - 1 / 3 )² = 10
(y / 2)² + 2 (y/2) (1/3) + (1/3)² - [(y/2)² - 2 (y/2) (1/3) + (1/3)² = 10
y² / 4 + 2 y /6 + 1/9 - [ y² / 4 - 2 y / 6 + 1/9 ] = 10
y² / 4 + 2 y / 6 + 1/9 - y² / 4 + 2 y / 6 - 1/9 =10
y²/4 -y²/4 + 2 y / 6 + 2 y /6 + 1/9 - 1/9 = 10
0 + 4 y /6 + 0 = 10
4 y / 6 = 10
m.m.c = 6
4 y = 60
y = 60/4
y = 15
(y / 2)² + 2 (y/2) (1/3) + (1/3)² - [(y/2)² - 2 (y/2) (1/3) + (1/3)² = 10
y² / 4 + 2 y /6 + 1/9 - [ y² / 4 - 2 y / 6 + 1/9 ] = 10
y² / 4 + 2 y / 6 + 1/9 - y² / 4 + 2 y / 6 - 1/9 =10
y²/4 -y²/4 + 2 y / 6 + 2 y /6 + 1/9 - 1/9 = 10
0 + 4 y /6 + 0 = 10
4 y / 6 = 10
m.m.c = 6
4 y = 60
y = 60/4
y = 15
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás